COMMUNICATIVE SITUATIONS: THE STANDARD AND THE CONFLICT ONES - Bihunov, Dmytro (PSYCHOLOGICAL JOURNAL, 2018)
The study of communicative situations is one of the most important areas of research in domestic and foreign science. The interaction of people and their contacts often give rise to collisions caused by contradictions of goals, views, interests, points of view etc., which, unfortunately, can lead to a conflict situation. If to talk about the standard communicative situation, it should be noted that most researchers pick out five or six its components, but often the same components get different names in different interpretations. Also it has repeatedly been emphasized that understanding between communicants is necessary for successful communication. Understanding occurs when interlocutors use the same linguistic code, if the communication channel is not blocked, and the communicators have the ability to encode and decode the information correctly, that is, they have the same system of codification and decoding of speech signs and signals. Thus, the processes of verbalization and understanding play a leading role in the implementation of the communicative act and, therefore, directly belong to its structure as the dominant components. The model of the standard communicative situation shows that the communicator (the addresser) with his/her own communicative goals communicates with the other communicator (the addressee), which also has certain communicative and practical goals, and implements the communicative text, using the appropriate code in certain circumstances. If communicants have similar ideas of the communicative goals of each other or towards the distribution of communicative roles, communication is realized in the form of cooperation. If the communicant chooses the wrong line of behaviour, the communicants’ intentions will lose their mutual agreement, and if they can not neutralize the negative impact of their actions on the communicative act, the latter may end up in a communicative failure (either complete or incomplete) and this leads to the emergence of communicative conflicts. In such a way, in live communicative situations the communicant simultaneously: a) perceives and accordingly evaluates information from the partner in the communication, b) calculates the type of relationships, which might be established with the partner in the communication. That is why both communicative failures and conflicts are not so rare. The conflict communicative situation is characterized by structural and dynamic characteristics. Structural characteristics include, as a rule, communicative discomfort, communicative failure, communicative inconsistency, communicative misunderstanding, communicative disputing, etc. These characteristics are explicated at the stages of the development of conflict situation. Stages of conflict situation consist of the pre-conflict stage (origin, maturation, incident), the stage of the conflict itself (conflict, conflict development), and the stage of the consequences of a conflict situation (or post-conflict situation). Dynamic characteristics of the conflict include, as a rule, the conditions and circumstances of the communication, the contradiction between the communicative and practical goals of the communicants, the results of communication, personal characteristics of the subjects of communication, as well as the situations of cognitive dissonance and “conflict-genes”, the violation of processes of verbalization and understanding, differences in social status of communicators, etc. From a practical point of view, the typology of conflict situations is very important, since it allows us to navigate through specific manifestations of conflict and, therefore, helps to assess possible ways of resolving them and achieving consensus.